Studi Komparatif Performa Framework Javascript Modern dalam Pengembangan Aplikasi Web - Octa Selsa Is Anggraeni; Lilik Sugiarto; Tinuk Agustin (Modem : Jurnal Informatika dan Sains Teknologi., 2024)
This research conducts a comparative study on the performance of modern JavaScript frameworks - React, Angular, and Vue.js - in the context of web application development. Using an experimental approach, this study measures various performance aspects including rendering time, bundle size, page load time, and memory usage. The research method involves developing web applications using all three frameworks in different scenarios, as well as interviews with experienced developers. Results show that Vue.js excels in rendering speed and memory efficiency, React demonstrates superiority in handling large-scale dynamic updates, while Angular offers a robust structured architecture. This study also reveals the importance of non-technical factors such as learning curve and community support in framework selection. In conclusion, the selection of an optimal framework should consider project-specific needs, team expertise, and long-term organizational goals. This research provides valuable insights for developers and organizations in choosing the appropriate JavaScript framework for their projects.